Assessment of Trimetazidine Treatment in Acute Myocardial Infarction Patients Undergoing Percutaneous Coronary Intervention. (2nd July 2022) - Tang, Xiuying; Gong, Jie
Abstract : Aims . Trimetazidine (TMZ) is effective at improving clinical outcomes in chronic heart failure and stable coronary artery disease patients. However, no single study has comprehensively evaluated the efficacy of TMZ in acute myocardial infarction (AMI) patients undergoing percutaneous coronary intervention (PCI). Methods . We enrolled 401 Chinese patients. All patients received the same drug prescription except for TMZ. In blinded fashion, patients were randomized to either a control or an experimental group in which 60 mg TMZ was provided at admission and then at 20 mg three times a day thereafter. At 2 and/or 6 days, we evaluated creatine kinase (CK and CK-MB), cardiac troponin I (cTnI), C-reaction protein (CRP), serum tumor necrosis factor (TNF- α ), serum creatinine (Cr), serum urea, glucose, glutamic pyruvic transaminase (ALT), and glutamic oxaloacetic transaminase (AST). Additionally, by echocardiography, we assessed left ventricular ejection fraction (LVEF), left ventricular end-diastolic dimension (LVEDD), and cardiac output (CO). Results . CK and CKMB, which were recorded on the second day in the hospital (each p = 0.022 ), and cTNI, which was recorded on the sixth day in the hospital (p = 0.003 ), were reduced with TMZ treatment compared to control. In addition, ALT and AST (p = 0.001, p = 0.000, respectively) and glucose after 6 days (p = 0.011 ) were significantly lower in the study group than in the control group. Furthermore, LVEF after 10–14 days and 6 months after discharge (p = 0.039 and p = 0.047, respectively) was increased with TMZ treatment. The effects of TMZ on CRP, TNF- α, Cr, urea, LVEDD, and CO were not significant (all p > 0.05 ). Conclusions . For AMI patients undergoing PCI, TMZ reduced circulating biomarkers of myocardial infarction, reduced values of ALT, AST, and glucose, and improved cardiac function compared with the control group.